(untitled) (Fiep Bulletin - online, 2013)
This study aims to present to the scientific community Santa Monica’s High School cultural sporting project (PEC) in response to notoriety and prominence reached in Rio de Janeiro. Foundation: This planning was divided into three sectors with a close relation among them, but its performances and dynamics are accomplished in independent ways. To develop this research, the theoretical points which give support to the Physical Education practice at a school environment were reviewed. Methodology: The referred study was developed in conformity with a descriptive layout. Conclusion: According to Santa Monica High School, as far as the role of a school of producing thinking individuals is concerned, Physical Education as a part of Education itself must be inserted in the pedagogical policy of a teaching institution. This insertion process needs to show Physical Education as a tool for learning, transmission, development and furtherance of values. Consequently, it will be legitimated and culturally incorporated to students, parents and community’s daily lives.